Figure 3 from: Heron J, Sheffield C (2016) First Canadian record of the water mite Thermacarus nevadensis Marshall, 1928 (Arachnida: Acariformes: Hydrachnidiae: Thermacaridae) from hot springs in British Columbia. Biodiversity Data Journal 4: e9550. https://doi.org/10.3897/BDJ.4.e9550 - Heron, Jennifer; Sheffield, Cory (Zenodo, 2016)
Figure 3 - Alpha Stream at Liard River Hot Springs Provincial Park in northeastern British Columbia. Photo by J. Heron.